THE POPULARITY OF MODERN TRANSPORT IN TASHKENT - Akhmedov Akbar Aktamovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: Tashkent, the capital of Uzbekistan, is undergoing a remarkable transformation as it embraces modern transport systems to address urbanization challenges and improve the quality of life for its residents. From electric buses and metro expansions to ride-sharing services and cycling infrastructure, modern transport solutions are gaining popularity in the city. Among these technologies, Unmanned Aerial Vehicles (UAVs), or drones, have gained significant popularity, becoming a symbol of Tashkent’s transformation into a smart and innovative metropolis. This article explores the growing role of UAVs in modern Tashkent and their impact on various aspects of urban life, the impact of modern transport on Tashkent’s urban landscape, and the challenges and opportunities that lie ahead.